Gender, older people and social exclusion: a gendered review and secondary analysis of the data - Emilia Del Bono; Emanuela Sala; Ruth Hancock; Caroline Gunnell; Lavinia Parisi (University of Essex, Institute for Social and Economic Research (ISER), 2007)
This study describes the conditions of older men and women in the UK and highlights gender differences in their degree of social inclusion, here defined with respect to: (i) use of services, (ii) provision of care, and (iii) participation in social networks. Using the 2001 Sample of Anonimised Records (SARs) we look at the current situation of older people (here defined as people aged 65 and over) in Britain. We document important gender imbalances in the age structure and marital status of older people, but point out that these differences will become less marked in the future according to the Government Actuarys projections. Using data from the General Household Survey we then investigate the extent of gender differences in older peoples degree of social inclusion. We find evidence that differences among older men and women with respect to service utilization, provision of informal care and participation in social networks are often the consequence of differences in marital status and living arrangements rather than gender differences per se.
Keywords: 330